2004
DOI: 10.33588/rn.3912.2004337
|View full text |Cite
|
Sign up to set email alerts
|

Trastorno específico del desarrollo del lenguaje: una aproximación teórica a su diagnóstico, etiología y manifestaciones clínicas

Abstract: INTRODUCCIÓN El trastorno específico del desarrollo del lenguaje (TEDL) se ha descrito con mayor rigor en los últimos 10 años. Autores como Bishop [1], Leonard [2], Narbona [3], Rapin [4], Allen [4] y Comti-Rasden [5] han contribuido de forma importante a la comprensión del tema y a su definición, así como a su clasificación para fines de agrupamiento, partiendo del análisis clínico de los síntomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
0
6
0
7
Order By: Relevance
“…Los trastornos del lenguaje en el niños desde el punto de vista neuropediátrico deberían clasificarse en tres grandes apartados: los trastornos específicos del lenguaje primarios, que corresponde al denominado trastorno específico del lenguaje, TEL-E, TEL-ER. El apelativo primario vendría reforzado por los recientes trabajos sobre genética molecular, la familia KE y la región crítica del cromosoma 7 conocida como SPCH1, así como la región conocida como FOXP2 y los recientes estudios de otros loci encontrados confirman la heterogeneidad genética y su trastorno primario [6].…”
Section: Discussionunclassified
“…Los trastornos del lenguaje en el niños desde el punto de vista neuropediátrico deberían clasificarse en tres grandes apartados: los trastornos específicos del lenguaje primarios, que corresponde al denominado trastorno específico del lenguaje, TEL-E, TEL-ER. El apelativo primario vendría reforzado por los recientes trabajos sobre genética molecular, la familia KE y la región crítica del cromosoma 7 conocida como SPCH1, así como la región conocida como FOXP2 y los recientes estudios de otros loci encontrados confirman la heterogeneidad genética y su trastorno primario [6].…”
Section: Discussionunclassified
“…The paper published by Nelson et al explains why the correct acquisition of language is of vital importance [8], while Fejerman stresses that a complete neurological and pediatric evaluation can reveal related developmental disorders, starting with detection of a language disorder [9]. Although medical procedures are available to detect a number of neurological disorders in children [4,10–12] these procedures are difficult to apply in primary pediatric care, as many require significant time and specialized knowledge. The review in this research found no solutions that exploit the potential of Information Systems in combination with artificial intelligence to provide pediatricians with efficient and effective assistance in the early detection of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The SLI refers to a primary language disorder that occurs in the absence of: hearing loss, speech cognitive and motor development alterations, syndromes, broad development disorders, sensorineural disorders, and acquired neurological lesions, and that impede the expected language development Castro-Rebolledo et al, 2004). It is a condition which the language difficulties persist through life (Gandara, 2004).…”
Section: Introductionmentioning
confidence: 99%